Measure Theory and Lebesgue Integration

Download as pptx, pdf, or txt
Download as pptx, pdf, or txt
You are on page 1of 23

MEASURE

THEORY AND
LEBESGUE
INTEGRATION

GROUP#2
TOPIC: STEP FUNCTION
GROUP MEMBERS :

Sadia Munir Iqra Iftikhar Humaira Zulfikar


(20011509-064) (20011509-064) (20011509-066)

Um-e-Zunaira Sana Ashfaq Nimra Iqbal


20011509-067) (20011509-068) (20011509-069)
What is the difference between step function and simple function?

Step Function Simple Function

STEP [𝑎, 𝑏] 𝑅 𝐸 𝑅
𝑓
FUNCTION 𝑓
=

AND 𝒇 ( 𝒙 ) =𝒄𝟐

SIMPLE
FUNCTION =

E is a measurable set.
A function f on a closed interval is said to be a step function if a
partition

STEP Of the interval such that in every subinterval


Then function f is constant,
FUNCTION
Here,
 A function defines as,

 Suppose that and


EXAMPLE
S:
7

𝑎 c b
This is the actual formation of step function
where are constants.
A signum function f defined as,

is a step function.
EXAMPLE
S 1
𝑥> 0

¿0 0 ¿0
𝑥< 0
-1
Every step function is a simple function but converse is not true.
Proof:
A function defined as

is a step function.

NOTE For simple function, we need measurable set.

As every closed interval is always a measurable set and its partitioned intervals are
measurable sets such that

 Intersection of any two open intervals is empty.

So, step function satisfy both conditions of simple function

And ineach open interval (), the value of f is constant.

. Hence f is a simple function.

Hence prove, every step function is a simple function


Converse is not true.

Every simple function may or may not be step function.

Define a function as

CONVERS Both are measurable set.

E R R
Q
𝒇 ( 𝒙 ) =𝟏
R-Q 𝒇 ( 𝒙 ) =𝟎

This is a simple function.

So this is not a step function because set of rational and irrational numbers are not intervals.
If and is disjoint measurable subsets of E then
Proof:
If and be disjoint measurable sets.
are measurable functions.
PREPOSITIO
So, and are bounded measurable functions.
N
Also,
PART (V)
Now,
Proof:
As we know that, if almost everywhere on E, then .

PREPOSITIO In particular, if ,

N Then,

PART (VI) Since, and


and
If 𝒇 = 𝒈 almost everywhere on E, then ‫𝒈 𝑬׬ = 𝒇 𝑬׬‬
Proof:
Since 𝑓 = 𝑔 almost everywhere on E
∴ 𝑓 − 𝑔 = 0 almost everywhere on E
Let 𝜓 be any simple function with 𝜓 ≥ 𝑓 − 𝑔
PREPOSTION
∴ 𝜓 ≥ 0 almost everywhere on E
PART(2) ‫ 𝐸׬ ≥ 𝜓 𝐸׬‬0 = 0

∴ න𝜓 ≥ 0
𝐸

for all simple function 𝜓 ≥ 𝑓 − 𝑔

∴ 𝐼𝑛𝑓 න 𝜓 ≥ 0
𝐸

𝜓 ≥ 𝑓 − 𝑔 as 𝜓 𝑖𝑠 𝑠𝑖𝑚𝑝𝑙𝑒 𝑓𝑢𝑛𝑐𝑡𝑖𝑜𝑛
‫ 𝑓( 𝐸׬‬− 𝑔) ≥ 0 ……….(1)
Let 𝜑 ≤ 𝑓 − 𝑔 be a simple function
∴ 𝜑 ≤ 0 almost everywhere on E

න𝜑 ≤ 0
𝐸

𝑆𝑢𝑝 න 𝜑 ≤ 0
𝐸

𝜑 ≤ 𝑓 − 𝑔 as 𝜑 is a simple function
‫ 𝑓( 𝐸׬‬− 𝑔) ≤ 0 ……….(2)
From eq 1 and eq 2

න𝑓 − න𝑔 = 0
𝐸 𝐸

න𝑓 = න𝑔
𝐸 𝐸

Hence Proved,
If 𝒇 ≤ 𝒈 almost everywhere in E, then ‫𝒈 𝑬׬ ≤ 𝒇 𝑬׬‬
Proof:
Since 𝑓 ≤ 𝑔 almost everywhere in E
PREPOSITION ∴𝑔−𝑓 ≥0
(3) Let 𝜓 be any simple function with 𝜓 ≥ 𝑔 − 𝑓
∴ 𝜓 ≥ 0 almost everywhere on E

∴ න𝜓 ≥ 0
𝐸

for all simple function 𝜓 ≥ 𝑔 − 𝑓

∴ 𝐼𝑛𝑓 න 𝜓 ≥ 0
𝐸

𝜓 ≥ 𝑔 − 𝑓 as 𝜓 𝑖𝑠 𝑠𝑖𝑚𝑝𝑙𝑒 𝑓𝑢𝑛𝑐𝑡𝑖𝑜𝑛

න𝑔 − 𝑓 ≥ 0
𝐸
න𝑔 − 𝑓 ≥ 0
𝐸

න𝑔 − න𝑓 = 0
𝐸 𝐸

න𝑔 ≥ න𝑓
𝐸 𝐸

Hence Proved,

You might also like

pFad - Phonifier reborn

Pfad - The Proxy pFad of © 2024 Garber Painting. All rights reserved.

Note: This service is not intended for secure transactions such as banking, social media, email, or purchasing. Use at your own risk. We assume no liability whatsoever for broken pages.


Alternative Proxies:

Alternative Proxy

pFad Proxy

pFad v3 Proxy

pFad v4 Proxy